MIGRATION FROM THE OAU TO THE AU: EXPLORING THE QUEST FOR A MORE EFFECTIVE AFRICAN PEACEKEEPING CAPABILITY - Thobane, Bruce; Neethling, Theo; Vreÿ, Francois (Scientia Militaria - South African Journal of Military Studies, 2011)
This thesis explores the quest for a more effective African peacekeeping capability. It seeks to answer the question what is different now that can enable the African Union (AU) to establish an effective peacekeeping capability after the Organisation of African Unity (OAU) failed to do so in the past. The study is a descriptive analysis of efforts by the AU to enhance its peacekeeping capabilities in resolving conflicts in Africa. The thesis traces the challenges that limited security cooperation and conditions that enhanced such cooperation in recent years, culminating in the approval of a continental standby force. It establishes that Africa was stagnated by security problems and at the same time it was reluctant to directly commit itself to resolve such problems, but instead sought assistance from the international community or relied on its own ad hoc arrangements. The study identifies the reason for this approach to have been the value of sovereignty entrenched in the OAU Charter, which forced leaders to pledge non-interference in each other’s internal affairs. The study further reveals that the establishment of the AU in 2000 was meant to give Africa the capability to resolve its own problems by consolidating intra-African security cooperation. The establishment of the Peace and Security Council (PSC) and its implementation tools such as the African Standby Force (ASF) opened a new window of hope in peace and security matters. However, the PSC is facing operational challenges, principally because of financial and logistical constraints, above its own lack of institutionalised mechanisms to ensure effective partnerships and burden sharing with its partners. This is against the revelation that the AU has insufficient capacity to embark on multidimensional peacekeeping operations on its own. This was highlighted by the AU peacekeeping operations in Burundi and Darfur (Sudan). The study concludes that although there is more political will, an improved continental security architecture and better United Nations-African cooperation, it is unlikely that the AU will be able to achieve an effective peacekeeping capability in the short to medium-term. This is against the backdrop that at the moment, the AU has severe limitations in both material and human resources. The AU is also unable to raise sufficient funds to pursue its peace and security agenda, and therefore the AU is still heavily dependent on external donors in its peacekeeping endeavours. However, the intended operationalisation of the ASF represents a promising achievement towards a long-standing Pan-African ideal that calls for “African solutions to African problems”.